Preparation method of high-temperature stealth coating based on ferromagnetic metal / phosphate interface optimization
By pretreating the metal substrate and curing it slowly at a higher temperature, combined with the use of surfactants and silicone oil, the problems of uncontrolled interfacial reaction and uncontrollable porosity in ferromagnetic metal/phosphate coatings were solved, improving the coating's bonding strength and high-temperature stealth performance, and achieving absorption effects across the entire X-band.
Patent Information
- Application Number
- CN202511686884.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-18
- Publication Date
- 2026-01-16
AI Technical Summary
Existing ferromagnetic metal/phosphate composite coatings suffer from uncontrolled interfacial reactions and uncontrollable porosity during preparation, leading to decreased mechanical properties and uneven radar absorption performance.
By pretreating the metal substrate, mixing phosphate adhesive, aggregate, curing agent and ferromagnetic metal absorber, and slowly heating and curing in an inert atmosphere, the interfacial reaction is suppressed and the porosity is controlled by the synergistic effect of surfactant and silicone oil.
It achieves a tight bond between the coating and the substrate, improves the mechanical strength and high-temperature stealth performance of the coating, and can achieve effective absorption across the entire X-band at 300℃. The preparation process is simple and applicable to ferromagnetic metal/phosphate coatings.
Smart Images

Figure CN121339017A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a method for preparing high-temperature stealth coatings based on ferromagnetic metal / phosphate interface optimization, belonging to the field of functional coating preparation technology. Background Technology
[0002] With the improvement of the performance of new generation aircraft equipment, the service temperature of hot-end components is constantly increasing. During the hypersonic penetration process, the local temperature of the windward position of supersonic fighter jets can reach 400-700℃ due to strong aerodynamic heating. Existing room temperature radar absorbing materials can hardly meet the requirements of high temperature stealth. Therefore, it is urgent to develop radar absorbing materials from room temperature high efficiency to extreme environment high efficiency.
[0003] The broadband absorption performance at low thicknesses often stems from the synergistic effect of dielectric and ferromagnetic losses. Ferromagnetic metals (such as Co, Fe, Ni, and their alloys) are irreplaceable absorber materials in high-temperature microwave absorbing coatings due to their excellent magnetic loss characteristics. Phosphate coatings offer advantages such as good high-temperature resistance, abrasion resistance, corrosion resistance, low cost, and environmental friendliness.
[0004] Chinese patent CN116239909B discloses a high-temperature stealth coating with adjustable microwave absorption performance and its preparation method, comprising the following components by weight fraction: 0-40% high-temperature ceramic aggregate; 30-50% phosphate adhesive; 5-10% curing agent; and 20-60% Co-based high-temperature absorber. The high-temperature stealth coating preparation method includes the following steps: S1, pretreating a metal substrate using micro-arc oxidation to pre-form a phosphate coating on the substrate surface; S2, mixing and stirring the high-temperature ceramic aggregate, phosphate adhesive, curing agent, and Co-based high-temperature absorber according to a preset mass fraction to prepare a coating; S3, applying the coating to the pretreated metal substrate surface, allowing it to harden at room temperature, transferring it to a high-temperature furnace for heat preservation, and obtaining a high-temperature stealth coating on the metal substrate surface after complete curing. This high-temperature stealth coating preparation technology has a simple process, and its effective absorption can be controlled within a wide range.
[0005] However, existing ferromagnetic metal / phosphate composite coatings suffer from technical bottlenecks such as uncontrolled interfacial reactions and uncontrollable porosity during preparation. During the composite coating preparation process, active elements in the ferromagnetic metal (such as Fe and Co) readily undergo redox reactions with phosphoric acid hydrolyzed from the phosphate, leading to the generation of a large amount of gas within the coating during curing. The numerous bubbles generated by this reaction not only restrict the coating's formation but also significantly reduce its mechanical properties. Furthermore, the uneven coating surface results in substantial differences in the coating's radar absorption performance. Summary of the Invention
[0006] This invention addresses the problems of uncontrolled interfacial reactions and uncontrollable porosity in the preparation of existing ferromagnetic metal / phosphate composite coatings, and proposes a high-temperature stealth coating preparation method based on ferromagnetic metal / phosphate interface optimization.
[0007] The technical solution adopted by the present invention to solve the above problems is as follows: The present invention includes the following steps: Step 1: Pre-treat the metal substrate; Step 2: Mix and stir the phosphate adhesive, aggregate, curing agent, ferromagnetic metal absorber and modified aqueous solution according to the preset mass fraction to prepare the coating; Step 3: Apply the prepared coating to the surface of the pretreated metal substrate, and place the coated metal substrate in an oven for slow heating and curing. Step 4: After the coating has cured, the metal substrate is placed in a muffle furnace with an inert atmosphere for high-temperature curing. After natural cooling, a high-temperature stealth coating is obtained on the surface of the metal substrate.
[0008] Furthermore, the metal substrate in step 1 includes, but is not limited to, one of the following: Ti-based substrate, Fe-based substrate, Al-based substrate, Ni-based high-temperature alloy substrate, and Co-based high-temperature alloy substrate.
[0009] Furthermore, the pretreatment steps for the metal substrate in step 1 include: Step 1.1: Perform mechanical processing on the metal substrate, wherein the mechanical processing is one of sanding, sandblasting and shot peening, to obtain a metal substrate with clean surface and adjusted roughness. Step 1.2: Activate the mechanically treated metal substrate, wherein the activation treatment is one of acid washing, alkaline washing and plasma cleaning, to obtain a metal substrate with increased surface active sites. Step 1.3: The activated metal substrate is sequentially cleaned with ethanol and deionized water and then naturally dried to complete the pretreatment of the metal substrate.
[0010] Furthermore, in step 2, the phosphate adhesive is one of the following: aluminum phosphate-based adhesive, zinc phosphate-based adhesive, magnesium phosphate-based adhesive, chromium phosphate-based adhesive, zirconium phosphate-based adhesive, silicon phosphate-based adhesive, and boron phosphate-based adhesive. The aggregate is a mixture of one or more of Al2O3, SiO2, SiC, TiO2, Si3N4, AlN, ZrO2, cordierite and mullite, with the size of Al2O3, SiO2, SiC, TiO2, Si3N4, AlN, ZrO2, cordierite and mullite being 100nm to 100μm; The curing agent is one of MgO, Al2O3, Al(OH)3, ZnO, Ca(OH)2, CuO, CaO, Fe2O3 and Cr2O3, and the size of MgO, Al2O3, Al(OH)3, ZnO, Ca(OH)2, CuO, CaO, Fe2O3 and Cr2O3 is 50nm to 10μm; The ferromagnetic metal absorber is a mixture of one or more of the following: spherical particles, flake particles, chain particles, dendritic particles, and rod particles. The size of the spherical particles, flake particles, chain particles, dendritic particles, and rod particles is 500 nm to 200 μm. The modified aqueous solution is composed of a surfactant, silicone oil, and deionized water. The surfactant is one of the following: 0.5-1.5 wt% cetyltrimethylammonium bromide, 0.5-1.5 wt% polysorbate-80, 1-2 wt% polyethylene glycol, 0.3-1 wt% KH550 or KH560, and 0.5-1.5 wt% sodium dodecyl sulfate. The silicone oil is one of the following: 0.1-2 wt% dimethyl silicone oil and 0.05-0.5 wt% polyether-modified silicone oil.
[0011] Furthermore, the preset quality fraction in step 2 includes: The mass fraction of phosphate adhesive is 40-60%, the mass fraction of aggregate is 15-30%, the mass fraction of curing agent is 5-15%, the mass fraction of ferromagnetic metal absorber is 0-50%, and the modified aqueous solution is 30-40% of the total mass of phosphate adhesive, aggregate, curing agent and ferromagnetic metal absorber.
[0012] Furthermore, the coating method in step 3 includes, but is not limited to, one of brushing, air spraying, and plasma spraying.
[0013] Furthermore, in step 3, the oven is set to heat up at a rate of 10°C / h during the slow curing process. After reaching 120°C, the oven is kept at that temperature for 12 hours to complete the curing.
[0014] Furthermore, in step 4, during the high-temperature curing process, the heating rate of the muffle furnace with inert atmosphere protection is set to 60℃ / h, and the temperature is raised to a selected temperature within the range of 200~600℃. After holding at the temperature for 2 hours, the curing is completed. By adjusting the selected temperature, stealth coatings with different phase structures and properties can be obtained.
[0015] The beneficial effects of this invention are: 1. This invention utilizes surfactants to optimize the interface between ferromagnetic metals and phosphates, inhibiting the reaction rate of ferromagnetic metal-phosphate and improving interfacial wettability, thus reducing bubble formation. Silicone oil, through its low surface tension, disrupts bubble stability and reduces system viscosity, promoting bubble escape. The synergistic effect of these two agents effectively solves the problems of interfacial reaction and porosity control in the preparation of ferromagnetic metal / phosphate coatings.
[0016] 2. The reduction in porosity gives the coating higher mechanical strength, and the bonding strength between the brush-applied coating and the titanium alloy substrate can reach 5.61 MPa.
[0017] 3. Based on the control of porosity, the high-temperature stealth performance of the coating can be controlled. At 300℃, the stealth coating can achieve effective absorption across the entire X-band.
[0018] 4. The preparation process of this invention is simple, significantly improves the morphology of the coating, and the prepared coating is tightly bonded to the substrate, not easily detached, and can achieve control over the high-temperature stealth performance of the coating. Furthermore, this invention is applicable to the preparation of ferromagnetic metal / phosphate coatings. Attached Figure Description
[0019] Figure 1 This is a schematic diagram of the process for preparing a high-temperature stealth coating based on the optimization of the ferromagnetic metal / phosphate interface; Figure 2 XRD patterns of Co / phosphate coatings after treatment at different curing temperatures; Figure 3 This is a schematic diagram of the Co / phosphate coating after standing for 20 minutes in Example 2; Figure 4 This is a schematic diagram of the unmodified Co / phosphate coating after standing for 20 minutes in Example 3; Figure 5 This is a cross-sectional SEM image of the Co / phosphate coating after curing in Example 2; Figure 6 This is a schematic diagram showing the bonding strength of the Co / phosphate coating after different temperature treatments in Example 2; Figure 7 This is a schematic diagram of the microwave absorption performance of the Co / phosphate coating at 300℃ in Example 2; Figure 8 The images show the surface and cross-section of the Co / phosphate coating after curing in Example 4. Figure 9 This is a flowchart of the pretreatment process for metal substrates. Detailed Implementation
[0020] Combination Figure 1This embodiment describes a method for preparing a high-temperature stealth coating based on ferromagnetic metal / phosphate interface optimization, comprising the following steps: S1: Metal substrate pretreatment to obtain a metal substrate with a clean surface and active sites; In this embodiment, the metal substrate includes, but is not limited to, one of Ti-based substrate, Fe-based substrate, Al-based substrate, Ni-based high-temperature alloy substrate, and Co-based high-temperature alloy substrate. In this embodiment, the applicable metal substrate is not limited, and any of the five types of substrates can be used to prepare the high-temperature stealth coating.
[0021] like Figure 9 As shown, the steps of metal substrate pretreatment include: S101. Mechanical processing of metal substrate; The mechanical treatment of the metal substrate includes one of sanding, sandblasting, and shot peening. In this step, the applicable mechanical treatment method for the metal substrate is not limited to any of the three methods, as all of them can achieve surface cleaning of the metal substrate while controlling its roughness. S102. Activation treatment of metal substrate; The mechanically treated metal substrate undergoes an activation treatment, which includes one of acid washing, alkaline washing, and plasma cleaning. In this step, the applicable activation treatment method is not limited to any of the three methods; all can increase the number of active sites on the surface of the metal substrate. S103. Cleaning of metal substrate; The activated metal substrate was cleaned with ethanol and deionized water and then air-dried.
[0022] Metal substrate pretreatment can remove grease, oxide film, impurities, etc. from the substrate surface, while increasing surface roughness and activating the surface chemical state, thereby improving the adhesion between the coating and the substrate.
[0023] S2: Prepare a coating by mixing and stirring phosphate adhesive, aggregate, curing agent, ferromagnetic metal absorber and modified aqueous solution according to a preset mass fraction; The phosphate adhesive is one of the following: aluminum phosphate-based adhesive, zinc phosphate-based adhesive, magnesium phosphate-based adhesive, chromium phosphate-based adhesive, zirconium phosphate-based adhesive, silicon phosphate-based adhesive, and boron phosphate-based adhesive. The aggregate is a mixture of one or more of Al2O3, SiO2, SiC, TiO2, Si3N4, AlN, ZrO2, cordierite and mullite, with the size of Al2O3, SiO2, SiC, TiO2, Si3N4, AlN, ZrO2, cordierite and mullite being 100nm to 100μm; The curing agent is one of MgO, Al2O3, Al(OH)3, ZnO, Ca(OH)2, CuO, CaO, Fe2O3 and Cr2O3, and the size of MgO, Al2O3, Al(OH)3, ZnO, Ca(OH)2, CuO, CaO, Fe2O3 and Cr2O3 is 50nm to 10μm; The ferromagnetic metal absorber is a mixture of one or more of the following: spherical particles, flake particles, chain particles, dendritic particles, and rod particles. The size of the spherical particles, flake particles, chain particles, dendritic particles, and rod particles is 500 nm to 200 μm. The modified aqueous solution is composed of a surfactant, silicone oil, and deionized water. The surfactant is one of the following: 0.5–1.5 wt% cetyltrimethylammonium bromide, 0.5–1.5 wt% polysorbate-80, 1–2 wt% polyethylene glycol, 0.3–1 wt% KH550 or KH560, and 0.5–1.5 wt% sodium dodecyl sulfate (based on the mass of the phosphate base material). The silicone oil is one of the following: 0.1–2 wt% dimethyl silicone oil and 0.05–0.5 wt% polyether-modified silicone oil (based on the mass of the phosphate base material).
[0024] In this embodiment, the surfactant adsorbs onto the surface of the ferromagnetic metal particles through hydrophobic interactions, forming an organic molecular film. This film hinders the absorption of H+ from phosphates. + Direct contact with the surface of ferromagnetic metal particles reduces the reaction rate. Furthermore, the amphiphilic nature of surfactants allows them to accumulate at the ferromagnetic metal particle-phosphate matrix interface, reducing interfacial tension and thus minimizing interfacial defects, promoting bubble coalescence and escape. Silicone oil can defoam by reducing surface tension and system viscosity. Therefore, the amount of surfactant can be precisely controlled to regulate the microstructure of the coating. The addition of surfactants can significantly inhibit the reaction between phosphate and ferromagnetic metals; however, excessive addition can lead to increased porosity on the coating surface. The addition of silicone oil can alleviate the surface porosity problem caused by excessive surfactant.
[0025] The preset mass fractions include: 40-60% phosphate adhesive, 15-30% aggregate, 5-15% curing agent, 0-50% ferromagnetic metal absorber, and the modified aqueous solution is 30-40% of the total mass of phosphate adhesive, aggregate, curing agent and ferromagnetic metal absorber.
[0026] In this embodiment, the electromagnetic properties of the high-temperature coating can be controlled by adjusting the type and filling rate of the ferromagnetic metal absorber.
[0027] S3: Apply the coating to the surface of the pretreated metal substrate and transfer it to an oven for slow heating and curing; In this embodiment, the coating is not limited to brush coating, air spraying and plasma spraying. The slow heating and curing in the oven is set to a heating rate of 10°C / hour for slow heating. After heating to 120°C, the temperature is held for 12 hours to complete the curing.
[0028] In this embodiment, the electromagnetic properties of the high-temperature coating can be controlled by adjusting the type and filling rate of the ferromagnetic metal absorber.
[0029] S4: The cured material is transferred to a muffle furnace under an inert atmosphere for high-temperature curing. After natural cooling, a high-temperature stealth coating is obtained on the surface of the metal substrate.
[0030] In this embodiment, the high-temperature curing in the muffle furnace under inert atmosphere protection is carried out at a heating rate of 60°C / hour and a curing temperature of 200-600°C. The curing temperature is maintained for 2 hours. By adjusting different curing temperatures, stealth coatings with different phase structures and properties can be obtained.
[0031] In this embodiment, the pre-cured coating is further cured to eliminate bound water within the coating and promote phase transformation of the various phases within the coating.
[0032] Example 1 The steps of the high-temperature stealth coating preparation method based on ferromagnetic metal / phosphate interface optimization described in this embodiment include: Step (1): The high-temperature alloy substrate (such as Inconel 718, Ti6Al4V) is subjected to surface sandblasting treatment with a roughness Ra=3-5μm. Then, it is subjected to plasma sputtering Ar ion cleaning and ultrasonic cleaning with ethanol and deionized water respectively. After drying, it is ready for use. Step (2): Weigh aluminum hydroxide and phosphoric acid in a molar ratio of 1:3. Specifically, weigh 83.04 g of 85% phosphoric acid solution into a beaker, weigh 18.72 g of aluminum hydroxide and dissolve it in 34.62 g of deionized water. Pour the aluminum hydroxide aqueous solution into the phosphoric acid solution which is heated and stirred in an 80°C water bath. After the reaction is complete and the solution is clear, stop the heating and stirring for half an hour. Take out the adhesive solution for later use.
[0033] Step (3): Take 10g of the above adhesive solution (of which the aluminum dihydrogen phosphate content is 56%), add 0.06g CTAB (based on 1% of the phosphate base material mass), stir for 30min, then add 0.1g dimethyl silicone oil (based on 1.8% of the phosphate base material mass) and stir for 30min to obtain the modified adhesive solution for later use.
[0034] Step (4): Weigh alumina nanoparticles, copper oxide and cobalt particles in the adhesive solution according to the mass ratio of adhesive solution: alumina nanoparticles: copper oxide: cobalt particles = 18:5:2:4 and add them to the adhesive solution. Stir for 2 hours to obtain a viscous and uniform coating.
[0035] Step (5): The coating is applied to the titanium alloy substrate obtained in step (1) by brushing. After 12 hours of natural drying, the sample is transferred to an oven for slow curing. The initial curing process is as follows: heating rate 10℃ / hour, heating to 120℃ and holding for 12 hours, then transferring to a muffle furnace under argon atmosphere protection, heating rate 60℃ / hour, heating to the curing temperature of 300℃ and holding for 2 hours, and after natural cooling, a high-temperature stealth coating is obtained on the surface of the metal substrate. Figure 2 XRD patterns of Co / phosphate coatings after treatment at different curing temperatures.
[0036] Example 2 The steps of the high-temperature stealth coating preparation method based on ferromagnetic metal / phosphate interface optimization described in this embodiment include: Step 1: Perform surface treatment on the titanium alloy substrate (Ti-6Al-4V, TC4). Use 80-200 grit sandpaper to polish the titanium alloy substrate in sequence to remove the oxide layer on the substrate surface. After polishing, use deionized water and anhydrous ethanol for ultrasonic cleaning to remove residual impurities on the substrate. After ensuring the substrate is clean, allow it to air dry naturally for later use.
[0037] Step 2: Weigh aluminum dihydrogen phosphate, alumina nanoparticles, copper oxide, and cobalt particles in a mass ratio of 10:5:2:4. Mix them evenly using a low-energy ball mill for 4 hours. Weigh the mixed powder for later use.
[0038] Step 3: Take 3.5g of deionized water in a beaker, add 0.045g of CTAB (0.9% of the phosphate base material by mass), and stir for 30 minutes. The white CTAB powder will completely dissolve and a large number of bubbles will be generated on the surface of the solution. Then add 0.1g of dimethyl silicone oil (2% of the phosphate base material by mass) and stir for 30 minutes to obtain the modified aqueous solution. Weigh the mixed powder into a beaker at a mass ratio of deionized water to mixed powder = 1:3. Stir the mixed slurry at room temperature for 2 hours to form a viscous and uniform coating. After the coating is placed in a plastic petri dish and left to stand for 20 minutes, the macroscopic morphology of its surface and sides is as follows. Figure 3 As shown.
[0039] Step 4: Apply the coating to the titanium alloy substrate obtained in Step 1 by brushing. After 12 hours of natural drying, transfer the sample to an oven for slow heating and curing. The initial curing process is as follows: heating rate 10℃ / hour, heating to 120℃ and holding for 12 hours. Then transfer to a muffle furnace under argon atmosphere protection, heating rate 60℃ / hour, heating to the curing temperature of 300℃ and holding for 2 hours. After natural cooling, a high-temperature stealth coating is obtained on the surface of the metal substrate.
[0040] Example 3 This embodiment is a comparison with Example 2, except that CTAB and dimethyl silicone oil were not added to the deionized water in step 3. The other steps are the same as in Example 2. After the coating prepared in this embodiment was placed in a plastic petri dish and allowed to stand for 20 minutes, its surface and side macroscopic morphology are as follows. Figure 4 As shown. With Figure 3 The comparison shows that after the cobalt / phosphate coating (modified with CTAB and dimethyl silicone oil) in Example 2 was left to stand for 20 minutes, no obvious pores were observed on the surface and sides, indicating that the interfacial reaction between the ferromagnetic metal cobalt and the phosphate matrix was effectively suppressed.
[0041] In this embodiment, the coating expanded due to the release of internal gas during the subsequent settling process, even overflowing the petri dish. After curing, the coating of Example 3, prepared by brush coating, exhibited severe blistering, and cross-sectional observation revealed a hollow internal structure and a significantly uneven surface. The coating of Example 2, prepared by brush coating, had a smooth, flat surface without blistering after curing; its microstructure is as follows... Figure 5 As shown, the coating contains only a small number of pores with a size of approximately tens of micrometers. The plate-like Co absorbent particles are clearly distributed within the matrix, and the particles exhibit good interfacial bonding with the phosphate matrix. Pull-out tests show that the bonding strength of the Co / phosphate coatings treated at different temperatures varies as follows: Figure 6 As shown, after heat treatment at 300℃, the bonding strength between the coating and the substrate reaches 5.61 MPa; Figure 7 As shown, when the coating thickness is 2.3 mm, effective absorption of electromagnetic waves in the entire X-band can be achieved at 300℃ (reflection loss RL < -10 dB).
[0042] Example 4 This embodiment is a comparison based on Embodiment 2. In step 3 of Embodiment 2, 0.01g of CTAB (0.2% of the mass of phosphate base material) is added to 3.5g of deionized water. The remaining steps are the same as in Embodiment 2.
[0043] The microstructure of the coating obtained in this embodiment is as follows: Figure 8As shown, the coating did not exhibit macroscopically visible pores as in Example 3 during the curing process, indicating that the reaction between cobalt and phosphate was suppressed. After curing, the coating surface was smooth and even, but the interior contained pores at the hundred-micron level, mainly attributed to the low amount of surfactant added, which only slightly inhibited the interfacial reaction between Co and phosphate. These results demonstrate that the porosity of the coating can be effectively controlled by precisely adjusting the amounts of CTAB and silicone oil added.
[0044] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent substitutions, and improvements made to the above embodiments without departing from the scope of the present invention, based on the technical essence of the present invention and within the spirit and principles of the present invention, shall still fall within the protection scope of the present invention.
Claims
1. A method for the preparation of high temperature stealth coatings based on the optimization of ferromagnetic metal / phosphate interface, characterized by, The application relates to a preparation method of a high-temperature stealth coating on a metal substrate. The application comprises the following steps: Step 1: pretreatment of the metal substrate; Step 2: mixing and stirring phosphate adhesive, aggregate, curing agent, ferromagnetic metal absorbent and modified water solution according to preset mass fractions to prepare a coating; Step 3: coating the prepared coating on the surface of the pretreated metal substrate, and placing the metal substrate coated with the coating into an oven for slow temperature rising and curing; 2. The method of claim 1, wherein the ferromagnetic metal / phosphate interface-optimized high-temperature stealth coating is prepared by a process comprising: Step 4: after the coating is cured, placing the metal substrate into a muffle furnace with inert atmosphere protection for high-temperature curing, and naturally cooling to obtain the high-temperature stealth coating on the surface of the metal substrate.
3. The method of claim 1, wherein the ferromagnetic metal / phosphate interface-optimized high-temperature stealth coating is prepared by a process comprising: The metal substrate in step 1 comprises but is not limited to one of a Ti-based substrate, an Fe-based substrate, an Al-based substrate, a Ni-based high-temperature alloy substrate and a Co-based high-temperature alloy substrate. The pretreatment steps of the metal substrate in step 1 comprise the following steps: Step 1.1: mechanical treatment of the metal substrate, wherein the mechanical treatment is one of sandpaper polishing, sand blasting and shot blasting, so that the metal substrate with a clean surface and adjusted roughness is obtained; Step 1.2: activation treatment of the metal substrate after the mechanical treatment, wherein the activation treatment is one of acid pickling, alkali washing and plasma cleaning, so that the metal substrate with increased surface active sites is obtained; 4. The method of claim 1, wherein the ferromagnetic metal / phosphate interface- optimized high-temperature stealth coating is prepared by a process comprising: Step 1.3: sequentially cleaning and naturally drying the metal substrate after the activation treatment with ethanol and deionized water, and completing the pretreatment of the metal substrate. The phosphate adhesive in step 2 is one of an aluminum phosphate-based adhesive, a zinc phosphate-based adhesive, a magnesium phosphate-based adhesive, a chromium phosphate-based adhesive, a zirconium phosphate-based adhesive, a silicon phosphate-based adhesive and a boron phosphate-based adhesive; The aggregate is a mixture of one or more combinations of Al2O3, SiO2, SiC, TiO2, Si3N4, AlN, ZrO2, cordierite and mullite, and the size of Al2O3, SiO2, SiC, TiO2, Si3N4, AlN, ZrO2, cordierite and mullite is 100 nm to 100 mu m; The curing agent is one of MgO, Al2O3, Al(OH)3, ZnO, Ca(OH)2, CuO, CaO, Fe2O3 and Cr2O3, and the size of MgO, Al2O3, Al(OH)3, ZnO, Ca(OH)2, CuO, CaO, Fe2O3 and Cr2O3 is 50 nm to 10 mu m; The ferromagnetic metal absorbent is one or more combinations of spherical particles, flaky particles, chain-shaped particles, dendritic particles and rod-shaped particles, and the size of the spherical particles, flaky particles, chain-shaped particles, dendritic particles and rod-shaped particles is 500 nm to 200 mu m; The modified water solution is composed of a surfactant, silicon oil and deionized water, wherein the surfactant is one of 0.5-1.5wt% hexadecyl trimethyl ammonium bromide, 0.5-1.5wt% polysorbate-80, 1-2wt% polyethylene glycol, 0.3-1wt% KH550 or KH560 and 0.5-1.5wt% sodium dodecyl sulfate, the silicon oil is one of 0.1-2wt% dimethyl silicone oil and 0.05-0.5wt% polyether modified silicone oil.
5. The method of claim 1, wherein the ferromagnetic metal / phosphate interface- optimized high-temperature stealth coating is prepared by a process comprising: The preset mass fraction in step 2 includes: The mass fraction of the phosphate adhesive is 40-60%, the mass fraction of the aggregate is 15-30%, the mass fraction of the curing agent is 5-15%, the mass fraction of the ferromagnetic metal absorber is 0-50%, and the modified water solution is 30-40% of the total mass of the phosphate adhesive, the aggregate, the curing agent and the ferromagnetic metal absorber.
6. The method of claim 1, wherein the ferromagnetic metal / phosphate interface- optimized high-temperature stealth coating is prepared by a process comprising: The coating method of the coating in step 3 includes but is not limited to one of brush coating, air spraying and plasma spraying.
7. The method for preparing a high temperature stealth coating based on ferromagnetic metal / phosphate interface optimization according to claim 1, characterized in that, In the slow temperature rising curing process in step 3, the temperature rising speed of the oven is set to 10 ℃ / h for slow temperature rising, and the curing is completed after the temperature is raised to 120 ℃ and the temperature is kept for 12 hours.
8. The method for preparing a high temperature stealth coating based on ferromagnetic metal / phosphate interface optimization according to claim 1, characterized in that, In the high temperature curing process in step 4, the temperature rising speed of the muffle furnace with inert atmosphere protection is set to 60 ℃ / h, the temperature is raised to a selected temperature in the range of 200-600 ℃, and the curing is completed after the temperature is kept for 2 hours; by adjusting the selected temperature, the stealth coating with different phase structures and properties can be obtained.
Citation Information
Patent Citations
A high-temperature stealth coating with adjustable wave-absorbing performance and a preparation method thereof
CN116239909B
